1994
DOI: 10.1093/brain/117.5.1169
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of gait hypokinesia in Parkinson's disease

Abstract: To identify the fundamental deficit in gait hypokinesia in Parkinson's disease (PD) we conducted a series of experiments that compared PD subjects with age- and height-matched controls in their capacity to regulate either stride length, cadence (steps per minute) or both parameters to three conditions. In the first condition the spatial and temporal parameters of gait were documented for slow, normal and fast walking. The second condition compared parkinsonian gait with the walking pattern of elderly controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
409
4
17

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(483 citation statements)
references
References 30 publications
41
409
4
17
Order By: Relevance
“…Concerning the dopaminergic pathway, both bradykinesia and PIGD have been associated with [ 123 I]β-CIT SPECT binding in patients with PD (Pirker 2003). Additionally, gait akinesia in PD was mainly attributed to an inability to increase step length (Morris et al 1994). Interestingly, by comparing Alzheimer's disease patients with increased MPS and those with decreased MPS, Camicioli et al have previously shown that patients with more MPS showed impaired spatial and variability gait parameters (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the dopaminergic pathway, both bradykinesia and PIGD have been associated with [ 123 I]β-CIT SPECT binding in patients with PD (Pirker 2003). Additionally, gait akinesia in PD was mainly attributed to an inability to increase step length (Morris et al 1994). Interestingly, by comparing Alzheimer's disease patients with increased MPS and those with decreased MPS, Camicioli et al have previously shown that patients with more MPS showed impaired spatial and variability gait parameters (2006).…”
Section: Discussionmentioning
confidence: 99%
“…One relevant group to investigate both with respect to locomotion as well as the sense of agency and voluntary motor control are patients suffering from Parkinson's disease. Gait-impairments such as asymmetry or freezing-of-gait are well documented (Browner and Giladi, 2010;Morris et al, 1994), as is the underlying pathology (Agid and Blin, 1987;Alexander et al, 1986), but beyond the scope of the current review. Although initial work on agencyrelated processing in Parkinsonism has been published by Moore et al (2010b), further research is required to systematically link such findings to models of sensorimotor control, locomotion, and upperlimb and gait agency.…”
Section: The Neuroscience Of Gait and Agencymentioning
confidence: 95%
“…2,10,[18][19][20] These studies also documented a tendency of longer duration in the double-support phase of the gait cycle and a normal cadence. In other studies, 21,22 a reduction of cadence values was reported.…”
Section: Spatiotemporalmentioning
confidence: 98%
“…Absence of dopamine in the basal ganglia circuit ultimately results in the loss of gait automaticity. Clinically, people with PD usually have the hallmark features of slowness (bradykinesia), 2 cessation of movement (akinesia), or freezing of gait. 3 As the disease advances, these gait disorders become more pronounced, disabling the patients and severely limiting their quality of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation